Therapeutic Potential of Peptides Derived from Animal Venoms: Current Views and Emerging Drugs for Diabetes. (March 2021) - Coulter-Parkhill, Aimee; McClean, Stephen; Gault, Victor A; Irwin, Nigel
The therapeutic potential of venom-derived drugs is evident today. Currently, several significant drugs are FDA approved for human use that descend directly from animal venom products, with others having undergone, or progressing through, clinical trials. In addition, there is growing awareness of the important cosmeceutical application of venom-derived products. The success of venom-derived compounds is linked to their increased bioactivity, specificity and stability when compared to synthetically engineered compounds. This review highlights advancements in venom-derived compounds for the treatment of diabetes and related disorders. Exendin-4, originating from the saliva of Gila monster lizard, represents proof-of-concept for this drug discovery pathway in diabetes. More recent evidence emphasises the potential of venom-derived compounds from bees, cone snails, sea anemones, scorpions, snakes and spiders to effectively manage glycaemic control. Such compounds could represent exciting exploitable scaffolds for future drug discovery in diabetes, as well as providing tools to allow for a better understanding of cell signalling pathways linked to insulin secretion and metabolism.